Laser Fluence Dependence of the Electrical Properties of MoO2 Formed by High Repetition Femtosecond Laser Pulses - Camacho, Santiago (2018)
Molybdenum oxides have gained attention in the last few years due to their vast variety of polymorphs. These materials relate to technological applications in several devices to exploit their chromic and electrical features, among others. Molybdenum oxide (MoO2 and Mo4O11) tracks are obtained in molybdenum thin films, deposited on glass substrates, by a previously reported (by our research group) optical technique based on femtosecond pulses from a Ti:sapphire laser oscillator. The present work reports on both the electrical resistance and resistivity of MoO2 tracks as a function of the per pulse laser fluence (Fp) used for the oxide synthesis. It is found that the electrical resistance, as well as the resistivity, of the MoO2 tracks drops as the delivered laser fluence is increased. The resistivity was determined to drop from 1.7 10 3Ωcm to 5 10 4Ωcm. This result agrees well with resistivity measurements reported in the literature for MoO2 nanosheets and films, respectively. This is explained by the fact that at low laser fluence the MoO2 forms a very thin surface layer, while for high laser fluences the MoO2 will get thick.